Behavioral Strategies and Policy Frameworks for Promoting Discipline in Child-Friendly School Environments - Tolero, Josue A.; Echaluse, Rhona Liza C. (Future Science / FSH-PH Publications, 2026)
This study investigates the implementation of behavioral strategies and their relationship with child-friendly school practices in public high schools within the Cabangan District. Utilizing a descriptive research design, the study surveyed teacher-respondents to assess their descriptions of behavioral strategies, including monitoring and evaluation, appropriateness, frequency, and consistency, as well as child-friendliness indicators such as teacher–student relationships, student engagement, and safety and orderliness. The collected data were analyzed using statistical tools such as percentage, weighted mean, ANOVA, and Pearson correlation. Findings indicate that teachers generally perceived behavioral strategies and child-friendliness positively, with active monitoring and appropriate strategies being the strongest areas, while frequency, consistency, and safety measures were identified as areas needing improvement. No significant differences were found in descriptions based on teacher profile variables, suggesting uniformity in understanding and implementation of policies. Pearson correlation revealed a weak positive but non-significant relationship between behavioral strategies and child-friendliness, implying that additional factors, such as leadership, resources, and parental involvement, also influence child-friendly practices. The study proposed a School-Based Behavioral Support Program to strengthen discipline and child-friendly practices. The program includes policy alignment, capacity building, monitoring and evaluation, restorative practices, and parent–community involvement, aiming to address areas of improvement and promote an inclusive, safe, and supportive school environment.